Audit Pricing, Start-Up Cost and Opinion Shopping - Oladipupo Muhrtala Tijani; Ahmad Bukola Uthman; Zayyad Abdul-Baki; Lukman Adebayo Oke (Journal of Accounting and Management Information Systems (JAMIS), 2014)
The purpose of this paper is to predict the association between the effect of start-up cost and audit opinion shopping on the pricing strategies of medium-sized audit firms. Using a sample of 753 local –office-year observations between 2006 and 2011, we find evidence of a positive association between higher audit pricing of new private client and audit opinion shopping. We also find that start-up cost is a good predictor of higher initial fees charged by auditors for private clients. While earnings risk management (ERM) and financial performance risk (FPR) are significant factors in audit pricing, litigation risk (LR) however failed to evolve as a direct significant predictor. Although this study focused on the effects of start-up costs and opinion reporting, it fails to differentiate between firm cost allocation and apportionment. The model can be used to assist audit firms not only to develop pricing strategies that fully reflect the effective cost allocation, but also to be receptive to the implications of opinion reporting on service pricing.
Keywords: M41; 650; Start-up cost; opinion shopping; audit pricing; medium-sized firms